COMPETENCY ANALYSIS OF PPKn TEACHERS IN THE APPLICATION OF LEARNING MODEL AT SMP NEGERI 8 SAMARINDA: ANALISIS KOMPETENSI GURU PPKn DALAM PENERAPAN MODEL PEMBELAJARAN DI SMP NEGERI 8 SAMARINDA - Liska Tandi Rerung; Endang Herliah; Aloysius Hardoko; Asnar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this research is to identify and describe the competence of PPKn teachers in the application of learning models in the learning process at SMP Negeri 8 Samarinda. aims to analyze the competence of Pancasila and Citizenship Education (PPKn) teachers in the application of the learning model at SMP Negeri 8 Samarinda. The teacher competencies studied include four main aspects, namely pedagogic competence, professional competence, personality competence, and social competence. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of three PPKn teachers who actively taught at SMP Negeri 8 Samarinda. The results of the study show that in general, PPKn teachers at SMP Negeri 8 Samarinda have a good understanding of various learning models such as cooperative learning models, group discussions, and problem-based learning. However, in practice, the implementation of the learning model has not been optimal due to several obstacles, such as limited time, inadequate learning facilities, and low student learning motivation. Teachers' pedagogic and professional competencies tend to be more prominent than personality and social competencies, which still need to be improved in the context of interaction with students and colleagues. Thus, improving teacher competence as a whole is important to support the effectiveness of the implementation of varied and innovative learning models, so that the learning goals of PPKn can be achieved optimally